Bibliometric Analysis of Brand Slogan in Event Tourism - Faezeh Abdollahnezhad; Reza Andam; Hassan Bahrololoum; Mojtaba Rajabi (Sports Business Journal)
Purpose: Marketing is a method that focuses on promoting companies' products and services. One of the main elements of promotion is the product or brand slogan. This study aimed to provide a bibliometric analysis of scientific documents on brand slogan research in event tourism.Methodology: This study used social network analysis to investigate co-authorship, co-occurrence of words, and cooperation coefficient. The research population consisted of studies of journals indexed in the Web Science database from 2006 to 2022, and 29 articles about brand slogans in tourism were selected as samples and analyzed using VOSviewer software.Findings: The results showed that research on brand slogans in tourism reached the highest level in 2017, and the United States did the most research in this area. The most frequently repeated words between 2014 and 2016 included destination brand, destination image, slogan, and marketing communications, and after 2016, the words "destination slogan" and "location identity" were repeated. Tourism slogans, logos, slogans, and products were the most frequent in 2020. Most citations were related to Lee's (2006) article. The differences between keywords before and after 2020 indicate the importance of slogan design and appropriate slogans for tourism brand marketing.Originality: It is suggested that tourism managers use the related slogan of their tourism brand to promote and market it. Also, the results of this research will help researchers to consider current issues in the field of event tourism in future studies and to identify authentic publications in the field of brand and tourism and use authentic articles to write their articles.